Considering the youth voice: needs and asset assessment in sport for development using photovoice - Tiesha Martin; Carrie LeCrom (Karolinum Press, 2021)
With the growth of sport for development (SFD), it is increasingly important to ensure that programmes are intentionally designed to meet the needs of the communities they serve, in a way that helps build community capacity. Still, many programmes have been criticised for not considering the voices of marginalised individuals, specifically youth programme recipients, in the planning and development of SFDprogrammes. Additionally, programmes are developed from a deficit approach where only the needs or negative aspects of the community are being considered in the planning and development of programming. With these issues in mind, the purpose of this study was to assess the usefulness of photovoice as a strategic tool to give youth a voice in SFD needs and asset assessment. Additionally, it examined how practitioners can utilize the outcomes of a needs and asset assessment in planning and implementing SFD programming. The results highlight the assets and challenges that the youth participants identified and the practical use of the assessment from the perspective of programme administrators. The results suggest that photovoice can allow youth programme participants to have a genuine voice in programme development.